Almost sure central limit theorem for self-normalized products of partial sums of negatively associated sequences. Issue 6 (19th March 2017) - Wu, Qunying
ABSTRACT: Let X, X 1, X 2, … be a stationary sequence of negatively associated positive random variables. A universal result in almost sure central limit theorem for the self-normalized products of partial sums is established, where .